Regenerative Tourism, Stakeholder Behavior, And Sustainable Business Transformation: A Systematic Literature Review - Cahya Nova Kurniawan; Almer Rasyid; Khabiza Mirzha Azzahra; Lydia Ery Octalina; Oktavia Dewi Rizka Alam (Relevance: Journal of Management and Business, 2026)
This study aims to clarify the conceptual ambiguity of regenerative tourism and examine how it contributes to stakeholder behavioral transformation. Using a systematic literature review approach, this study analyzed 62 peer-reviewed articles through thematic synthesis involving open, axial, and selective coding. The findings show that regenerative tourism can be structured into four interrelated layers: ontological foundation, domain orientation, governance and system structure, and operational logic. The review also identifies six behavioral transformation pathways: experiential, cognitive-value, social-relational, institutional, technological, and empowerment pathways. Among these, empowerment emerges as a central mechanism linking governance structures to individual and collective agency. This study contributes to management and business literature by positioning regenerative tourism as a strategic framework for stakeholder engagement, destination governance, sustainable business models, and community-based value creation. The proposed framework offers a basis for future empirical testing and provides practical guidance for tourism managers, destination organizations, and policymakers seeking to design more inclusive and regenerative tourism practices.